Shared parenting, law and policy: considering power within the framework of autopoietic theory. Issue 4 (2nd November 2015) - Newnham, Annika
Abstract: This paper uses the last few decades' developments in the area of shared parenting to explore power within the framework of autopoietic theory. It traces how, prompted by turbulence from the political subsystem, family law has made several unsuccessful attempts to solve the perceived problem of post-separation dual-household parenting. It agrees with Luhmann and Teubner that closed autopoietic systems' developments are limited by their normative and cognitive frameworks, and also argues that changes which have occurred in family law show that closed social systems do not function in total isolation. It considers power as ego 's ability to limit alter 's choices. In our functionally differentiated society, with its recent proliferation of communication, power appears more diffuse and impossible to plot into causal one-way relationships.